2006
DOI: 10.1016/j.intcom.2005.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Towards culture-centred design

Abstract: This paper addresses culturally rooted factors within user interface design. The design implications of globalisation are discussed, together with the related processes of internationalisation, localisation, ‘glocalisation’, iconisation and culturalisation, in order to establish a basis for a new approach to HCI design. The potential for a more diverse culture-centred, design-based system—‘Culture-Centred Design’ (CCD) is introduced, and a CCD process developed.\ud \ud A redesigned computer interface, incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 10 publications
(8 reference statements)
1
68
1
1
Order By: Relevance
“…This study added to the wealth of evidence that users from different cultures can perceive webpages differently and often prefer different designs [1][2][3][4][5][6][25][26]. We suggested that designers should understand the preferences of users from diverse cultures and provide specific designs to address their preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study added to the wealth of evidence that users from different cultures can perceive webpages differently and often prefer different designs [1][2][3][4][5][6][25][26]. We suggested that designers should understand the preferences of users from diverse cultures and provide specific designs to address their preferences.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of studies has revealed a cross-cultural difference in user preferences and judgments on the webpage design [1][2][3][4][5][6]. For instance, Simon [6] found that Asians disliked triangles and squares on webpages, whereas North Americans and Europeans preferred combinations of those shapes.…”
Section: Cross-cultural Difference In Preferences Of Webpage Designmentioning
confidence: 99%
“…We then compared these with CultureCentred Design (CCD) (culturally specific) icons that aim to differentiate from standardised ones, and have been designed specifically for Chinese users [13]. Eight basic Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Design of visual information is produced by visual medium for people to pass on messages, and the design of information is at its center, with visual perception design as its soul, and mutual design as its essence. A study has shown that culture-centred design of interface demonstrated very positive feedbacks from users [4]. Cultural patterns have significant influences on the product design conceptualization [5].…”
Section: B Information Visualization 1) Information Design and Visuamentioning
confidence: 99%